TEMPORO-MANDIBULAR JOINT. THE FEATURES OF FUNCTIONAL ANATOMY AND HISTOLOGICAL STRUCTURE DURING THE DYSFUNCTION OF TMJ - L.I. Shkilniak; A.A. Zalyziuk-Krapivna (Український стоматологічний альманах)
The question of structural organization, function and diagnosis of the diseases of temporomandibular joint (TMJ) has attracted the attention of various specialists for a long time. To date, there is no data about morphological and functional status of tissues and organs of maxillofacial region during the TMJ dysfunction and different defects, accompanied by a decrease in the height of the lower third of the face.